Why I declare a conflict of interest and you should not - Acem, Ensar; Aczel, Balazs; Albayrak, Nihan; Brown, Nicholas J. L.; Dudda, Leonie A.; Elsherif, Mahmoud Medhat; Gjoneska, Biljana; Kowal, Marta; Krishna, Anand; Miłkoś, Szymon; Paruzel-Czachura, Mariola; Patel, Jay; et al. (Theory and Society)
Academic publishing is both an indication of scientific contribution and a currency for career advancement. This dual role gives rise to a normative scientific conflict: Does the structural incentive to publish constitute a conflict of interest (COI) that ought to be disclosed? In this paper, we address this conflict through an action research approach, engaging collaboratively and reflexively to answer four related questions: (1) What evidence suggests that researchers face a (financial) COI when publishing? (2) What are the benefits and drawbacks of explicitly acknowledging that publications function as academic currency? (3) How should such conflicts be disclosed? (4) Do mechanisms such as pre-registration and registered reports resolve these concerns? This paper contends that while researchers are clearly incentivised to publish, this interest need not necessarily constitute a conflict or be explicitly disclosed. Treating this issue as a normative scientific conflict does reveal the need for a shift in how researchers understand and navigate the subjective, self-interested dimensions of their work. We propose four key responses: (1) integrating discussions of COIs and biases more extensively into undergraduate science education, (2) promoting greater reflexivity in everyday research practice (e.g., through reflexivity journals, peer-led audit groups, and the reintegration of discussions on the historicity and cultural nature of research into scientific publications), (3) critically investigating institutional incentives and journal policies, and (4) proactively adopting methodological safeguards such as pre-registration. By addressing this conflict through action research, we demonstrate how normative tensions in science can be made productive — supporting both critical reflection and structural improvement.

No Student Should Be an Island: A Peer-Approach to Decoding and Disrupting - Schmöckel, Sabrina; Scharlau, Ingrid (Transformative Dialogues: Teaching and Learning Journal)
his article describes a new student-based approach to Decoding and Disrupting. This approach consists of an educational programme that works with a multidisciplinary group of undergraduate students, so-called Culture Fellows. In the programme, the students learn about theories on disciplinary cultures and their practices, Decoding the Disciplines, and communication. The programme focuses on the implicitness of disciplinary practices and how to explore them, i.e., it seeks to address the importance of making disciplinary practices, norms, and values more accessible to students. Within the programme, the Culture Fellows use a student-based variant of the Decoding the Disciplines Paradigm that we call ‘Culture Quest’. The Culture Quest supplies students with the tools to question, explore, and decode their respective disciplines and practices. Disciplinary practices often remain implicit because lecturers, with their wealth of experience and expertise in their discipline, may be operationally blind and thus no longer aware of the fact that certain practices might need to be explained. This lack of explanation or explicitness can lead to students feeling bewildered, confused or puzzled. The Culture Fellows and in particular the Culture Quest can encourage dialogue about and exploration of disciplinary cultures and their practices and can thus allow students to grasp the implicit cultural norms and expectations within their respective disciplines more clearly. The Culture Fellows and the Culture Quest provide students – and maybe even lecturers – with opportunities to engage with and reflect on teaching and learning strategies and practices.

Hör mal, wer da spricht – Eine dialogische Perspektive auf studentische Äußerungen zu Fachkulturen - Schmöckel, Sabrina (die hochschullehre)

Healthy Distrust in AI systems - Paaßen, Benjamin; Alpsancar, Suzana; Matzner, Tobias; Scharlau, Ingrid (arXiv)
nder the slogan of trustworthy AI, much of contemporary AI research is focused on designing AI systems and usage practices that inspire human trust and, thus, enhance adoption of AI systems. However, a person affected by an AI system may not be convinced by AI system design alone---neither should they, if the AI system is embedded in a social context that gives good reason to believe that it is used in tension with a person’s interest. In such cases, distrust in the system may be justified and necessary to build meaningful trust in the first place. We propose the term healthy distrust to describe such a justified, careful stance towards certain AI usage practices. We investigate prior notions of trust and distrust in computer science, sociology, history, psychology, and philosophy, outline a remaining gap that healthy distrust might fill and conceptualize healthy distrust as a crucial part for AI usage that respects human autonomy.

What do metaphors of understanding hide? - Porwol, Philip Fabian; Scharlau, Ingrid (STUDIA NEOFILOLOGICZ: NEROZPRAWY JĘZYKOZNAWCZE (Modern Language Studies: Linguistic Essays))
Many previous studies on the conceptual function of metaphors have focused on their func-tion of highlighting aspects of target concepts. From the beginning of this research, it was knownthat conceptual metaphors also hide aspects of the target concept; however, this as-pect has been less studied. This study builds upon the idea that the hiding aspect of a specific metaphor should be identified in relation to other metaphors for the same concept. A method is presented to detail this relation based on the theory of semantic frames and the FrameNet resource to identify the hidden aspects and apply it to a corpus of 298 elicited metaphor texts on the target concept of understanding. The analysis revealed that certain conceptual aspects are consistently hidden by a majority of metaphors, pointing to patterns in conceptualization. Using this approach, six aspects frequently hidden by metaphors were identified: Sociality, Transfer, Ownership, Perception, Foundation and Duration.

Didaktische Überlegungen in der Psychologie - Scharlau, Ingrid; Jenert, Tobias (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

Bildung und Lesesozialisation im Elternhaus - Buhl, Heike M.; Hilkenmeier, Johanna (Handbuch Entwicklungs- und Erziehungspsychologie)

Impact of felt obligation and perceived mutual reciprocity on support between mothers and their adult children - Schoenert, Kathrin; Sommer, Sabrina; Buhl, Heike M. (Frontiers in Developmental Psychology)

Students’ personality impacts sense of belonging of students in different ways - Bohndick, Carla; Breetzke, Jonas; Klingsieck, Katrin B.; Buhl, Heike M. (Social Psychology of Education)

Intra-individual variability in TVA attentional capacity and weight distribution: A reanalysis across days and an experiment within-day - Banh, Ngoc Chi; Scharlau, Ingrid
The present article offers an assessment of intra-individual variability in visualattention using the Theory of Visual Attention, which provides a formal framework forquantifying attentional components. We specifically investigated overall attentionalcapacity – that is, the available processing speed – and its distribution, the relativeattentional weight.By reanalyzing a large existing dataset from Tünnermann and Scharlau (2021),we found that across multiple testing days, participants either remained stable within a20 Hz margin or showed consistent improvements in capacity – in some cases triplingtheir initial capacity. The weights in response to salient stimuli were remarkablyconsistent.To determine whether increases in capacity reflect pure test-retest effects or arefacilitated by consolidation between days, and to quantify within-day variability, weconducted a second study in which participants completed five self-administeredsessions within a single day. Capacities remained within the same magnitude and didnot show a consistent directional trend. The relative weights exhibited comparativelylittle variation in most participants, akin to the previously analyzed dataset. Further,estimation uncertainty increased with higher capacity values.These results suggest that capacity may be subject to training effects, but thatsuch improvements appear to depend on longer breaks between sessions. This hasimportant implications for individualized assessment: A personal prior could beestimated from a single session to accelerate future estimations, as long as subsequentsessions occur on the same day. Participants with higher capacities may require tailoredexperimentation methods when small to medium effects are of interest, due to increaseduncertainty.

Digitale Ressourcen im Psychologieunterricht - Brucks , Tabea; Buhl, Heike M. (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen. Ein Lehrbuch mit Unterrichtsmaterialien)

„Wir wollen mitreden!“ – Entwicklung und Validierung von Skalen zur Erfassung motivationaler Regulation bei der Teilnahme an Befragungen zur Evaluation des Studiums (SMR-Eval) - Koppenborg, Markus; Klingsieck, Katrin B. (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung: Für die Evaluation und Qualitätsentwicklung von Studium und Lehre werden häufig quantitative Befragungen von Studenten eingesetzt. Jedoch ist häufig unklar, aus welcher Motivation Studenten an den Befragungen teilnehmen und inwieweit unterschiedliche motivationale Regulationsstile mit dem Antwortverhalten im Fragebogen zusammenhängen. Ausgehend von der Selbstbestimmungstheorie der Motivation nach Deci und Ryan stellt der Beitrag die Entwicklung der Skalen zur motivationalen Regulation bei Befragungen zur Evaluation (SMR-Eval) vor. Studie 1 zeigt die fünffaktorielle Struktur des Instruments. Studie 2 weist auf eine starke Messinvarianz bezüglich Geschlecht, Abschlussziel und Fakultät hin. Korrelationen mit Drittvariablen belegen die konvergente Validität der fünf Subskalen. In Studie 3 werden latente Profilanalysen über die fünf Regulationsstile berechnet. Die Ergebnisse zeigen vier Profile, welche sich inhaltlich plausibel im Antwortverhalten der Befragten unterscheiden und damit Hinweise auf die Kriteriumsvalidität der Skalen geben. Diskutiert werden theoretische und praktische Implikationen für Evaluationsvorhaben an Hochschulen sowie Übertragungsmöglichkeiten auf andere Evaluationsgegenstände.
Keywords: Developmental and Educational Psychology

Effects of task difficulty on visual processing speed - Banh, Ngoc Chi; Scharlau, Ingrid

Safety Assistance Systems for Bicyclists: Toward Empirical Studies of the Dooring Problem - Stratmann, Lukas; Banh, Ngoc Chi; Scharlau, Ingrid; Dressler, Falko (ACM Symposium on Principles of Distributed Computing (PODC 2024), Advanced tools, programming languages, and PLatforms for Implementing and Evaluating algorithms for Distributed systems (ApPLIED 2024))
To reach the goal of zero traffic fatalities a year, one building block is the proposition to develop advanced assistance systems for vulnerable road users (VRUs) such as bicyclists. We focus on the dooring problem, i.e., car doors being opened inattentively in the way of an approaching cyclist. We extended our vehicle to everything (V2X) communication-enabled virtual cycling environment for dooring experiments. Our system extends toolkits that are widely used in the V2X research community. We showcase how such a system may be used to realize and evaluate distributed algorithms for VRU safety solutions such as dooring prevention.

Analyzing student response processes to refine and validate a competency model and competency-based assessment task types - Soyka, Chantal; Schaper, Niclas (Frontiers in Education)

Measuring Visual Attention Capacity Across xReality - Biermeier, Kai; Scharlau, Ingrid; Yigitbas, Enes (Proceedings of the 17th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2024))
Augmented (AR) and Virtual Reality (VR) technologies have been applied very broadly in the recent past. While prior work emphasizes the potential of these technologies in various application domains, the process of visual attention in and across the contexts of AR/VR environments is not exhaustively explored yet. By now, visual attention in AR/VR environments has majorly been studied by means of overt attention (i.e. saccadic eye movements), self-report, and process-related visual attention proxies (like reaction time). In this work, we analyze covert visual attention based on the (psychological) Theory of Visual Attention (TVA), which allows us to quantify theory-based interpretable properties of the visual attention process. For example, the TVA allows us to measure the overall processing speed. We instantiate this TVA-based framework with a 30-participant explorative within-subjects study. The results show a decisive difference in visual attention between Reality (i.e. the neutral condition) and Virtual Reality and a weak difference between Reality and Augmented Reality. We discuss the consequences of our findings and provide ideas for future studies.
Keywords: Visual Attention; TVA; Cognitive Modelling; Bayesian Modelling; AR; VR

Trait- and State-Aspects of Procrastination and Their Relation to Study Satisfaction - Koppenborg, Markus; Ebert, Anna; Klingsieck, Katrin B. (European Journal of Psychological Assessment)
Abstract: Research differentiates between procrastination as a trait and as a state. While trait procrastination implies cross-temporal stability, state procrastination denotes an episode in which a particular task is procrastinated, therefore implying cross-temporal variability. However, it is unclear whether trait procrastination scales (i) capture temporal-variable variance components (i.e., state procrastination), and (ii) how trait and state are differentially related to other variables commonly associated with procrastination. Latent state-trait modeling was used to separate stable from temporal-variable variance components of a common trait procrastination measure and to relate both facets of procrastination to satisfaction with the studies as an example for related variables. Student participants ( N = 194) filled out the five-item short version of the General Procrastination Scale (GPS; Klein et al., 2019 ) three times with 12-month intervals between each measurement. Results confirm that GPS scores reflect stable components of procrastination to a larger extent than temporal-variable variance components. And they demonstrate that variable procrastination correlates more strongly with study satisfaction, as compared to stable procrastination. These results may inspire research to specify how far correlates of procrastination pertain to trait procrastination, state procrastination, or both.

Procrastination – Having, or Not Having Self-Access, That Is the Question - Klingsieck, Katrin B. (European Psychologist)
Abstract: There is ample theoretical and empirical support for the idea that both conscious and unconscious volitional processes, predecisional and postdecisional aspects, and the aspect of having or not having self-access play a role in procrastination episodes. The unconscious volitional processes, predecisional aspects, and the aspect of self-access are yet rather under-researched. If they are considered, however, procrastination can be understood on an even deeper level and treated more sustainably. Moreover, considering these aspects opens up a humanistic perspective on procrastination episodes, thereby, putting procrastination and procrastination interventions in the bigger picture of self-actualization, self-alienation, and self-growth.

Knowledge telling und knowledge transforming. Eine dialogische Perspektive - Stock, Ingrid; Karsten, Andrea; Eik-Nes, Nancy Lea (40 Begriffe für eine Schreibwissenschaft. Konzeptuelle Perspektiven auf Praxis und Praktiken des Schreibens)

Stimme. Eine dialogische Perspektive - Karsten, Andrea; Bertau, Marie-Cécile (40 Begriffe für eine Schreibwissenschaft. Konzeptuelle Perspektiven auf Praxis und Praktiken des Schreibens)